Functional teleology and the coherence of Ephesians a comparative and reception-historical approach - Covington, Eric 1986- (Tübingen Mohr Siebeck, 2018)
Cover -- Preface -- Table of Contents -- List of Abbreviations -- Chapter 1: Introduction -- Chapter 2: The Question of Coherence in Ephesians -- 2.1. Introduction -- 2.2. The Conceptual Coherence of Ephesians in Recent Scholarship -- 2.2.1. Ephesians and Post-1940s Ecclesiology -- 2.2.2. Ephesians and Gnosticism -- 2.2.3. Ephesians in Modern Comparative Study -- 2.2.4. Ephesians and Greco-Roman Rhetoric -- 2.2.5. Ephesians and Ancient Political Philosophy -- 2.2.6. Ephesians and Ancient Folk Religion -- 2.2.7. Ephesians and Socio-Scientific Studies -- 2.2.8. Summary: The Problem of Conceptual Coherence in Ephesians -- 2.3. Observation: Modern Virtue Ethics and Ancient Ethical Thought -- 2.3.1. Telos and Human Function in Ancient Ethical Thought -- 2.3.2. The Erosion and Inversion of Teleological Thought in Modernity -- 2.4. Hypothesis, Aims, and Structure -- 2.4.1. Hypothesis: Ephesians and the Logic of Functional Teleology -- 2.4.2. Previous Teleological Approaches in New Testament Studies -- 2.4.3. Preliminary Definitions -- 2.4.4. Aims and Structure -- 2.5. Method and Methodology -- 2.5.1. Reading Ephesians within the Ancient Thought World -- 2.5.2. Analogical Comparative Studies in Biblical and Ancient Philosophical Ethics -- 2.5.3. Auslegungsgeschichte and the Interpretation of Ephesians -- Part One: Functional Teleology in the Ancient Thought World -- Chapter 3: Teleology in Ancient Ethical Thought -- 3.1. Introduction -- 3.2. The Tablet of Cebes and Ancient Teleological Ethics -- 3.2.1. The Tablet of Cebes -- 3.2.2. Teleological Ethics and The Tablet of Cebes -- 3.2.3. Teleology in Ancient Ethics -- 3.3. The Corporeal Metaphor, Teleology, and the Functional Argument -- 3.3.1. The Corporeal Metaphor and the Functional Argument in Aristotle -- 3.3.2. The Corporeal Metaphor and the Functional Argument in Other Ethical Traditions
3.4. Functional Teleology: A Précis of Ancient Teleological Coherence -- 3.5. Conclusion -- Chapter 4: Functional Teleology in Ancient Ethical Traditions -- 4.1. Introduction -- 4.2. Functional Teleology in Epicureanism -- 4.2.1. Cosmology -- 4.2.2. Teleology -- 4.2.3. Teleological Ethics -- 4.3. Functional Teleology in Stoicism -- 4.3.1. Cosmology -- 4.3.2. Teleology -- 4.3.3. Teleological Ethics -- 4.4. Functional Teleology in Early Jewish Writings -- 4.4.1. Functional Teleology in 1 Enoch 1-5 -- 4.4.2. Functional Teleology in Sirach -- 4.4.3. Functional Teleology in Wisdom of Solomon -- 4.5. Conclusion -- Part Two: Functional Teleology in Thomas Aquinas' ad Ephesios -- Chapter 5: Aquinas' ad Ephesios in Context -- 5.1. Introduction -- 5.2. Aquinas as Exegete -- 5.3. Aquinas as Theological Exegete: On the Basis of Divine Revelation -- 5.4. Aquinas as Philosophical-Theological Exegete: The Use of Human Reason and Logic -- 5.4.1. The Essence/Existence Divide and Movement from Potential to Actual -- 5.4.2. Functional Teleology: Perfection and Completion in Complex Systems -- 5.4.3. Human Teleology: The Beatific Vision as Ultimus Finis -- 5.4.4. Teleology in Human Ethics and Behavior -- 5.5. Conclusion: Aquinas as Biblical Exegete at the Horizons of Philosophical-Theological Interpretation -- Chapter 6: Functional Teleology in Aquinas' ad Ephesios -- 6.1. Introduction -- 6.2. Prologue to the Lectura -- 6.3. Epistolary Greeting: Ephesians 1:1-2 -- 6.4. Strengthening the Church in Good Habits: Ephesians 1:3-3:21 -- 6.4.1. Divine Blessings Given Through Christ (Eph 1:3-21) -- 6.4.2. Blessings in Relation to their Former Condition (Eph 2:1-22) -- 6.4.3. The Blessing of the Revelation of the Mystery to Paul (Eph 3:1-21) -- 6.5. Spurring Them on to Greater Good: Ephesians 4:1-6:9 -- 6.5.1. Admonition to Preserve Ecclesial Unity (Eph 4:1-16)
6.5.2. Precepts for Preserving Unity (Eph 4:17-6:9) -- 6. The Power for Accomplishing Unity: Ephesians 6:10-24 -- 7. Conclusion -- Part Three: Functional Teleology in Ephesians -- Chapter 7: The Teleological Cosmology of Ephesians -- 7.1. Introduction -- 7.2. The Eulogy and the Ephesian Weltbild -- 7.2.1. God's Establishment of Cosmic Purpose in 1:4-6 -- 7.2.2. The Ultimus Finis of All Things: Anakephalaiosis and the Praise of God's Glory -- 7.3. The Enthronement of Christ and the Ephesian Weltbild -- 7.4. Christ's Descent and Ascent and the Ephesian Weltbild -- 5. Summary -- Chapter 8: Functional Teleology in Ephesians -- 8.1. Introduction -- 8.2. Function and Purpose: Attaining the ????? ??????? -- 8.2.1. The Corporeal Metaphor and the Function of Individual Members: Eph 4:11-16 -- 8.2.2. The Ultimus Finis of the Ecclesial Gifts: Eph 4:13 -- 8.3. Telic Perspectives in the Eulogy -- 8.3.1. Elected and Predestined for a Purpose: Eph 1:3-5 -- 8.3.2. The Earnest of the Inheritance: Eph 1:13-14 -- 8.4. Telos and Ekklesia -- 8.4.1. The New Humanity and the Unified Church: Ephesians 2 -- 8.4.2. The Political Metaphor: Eph 2:19 -- 8.4.3. The Architectural Metaphor: Eph 2:20-22 -- 8.5. The Ecclesial Telos within the Cosmic Anakephalaiosis -- 8.6. Summary -- Chapter 9: Teleological Ethics in Ephesians -- 9.1. Introduction -- 9.2. Where Do the "Ethics" Begin? -- 9.3. The Teleological Basis of Ethics in Ephesians -- 9.4. Living as the New Humanity -- 9.5. Living as One Who Will Attain the Inheritance -- 9.6. The Haustafel: Teleological Ethics within the Household -- 9.7. The Armor of God: Living in the Cosmic System -- 9.8. Conclusion -- Part Four: Eis to Telos -- Chapter 10: Reading Ephesians through the Lens of Functional Teleology -- 10.1. Overview -- 10.2. Functional Teleology and the Coherence of Ephesians
10.3. Functional Teleology and the "Doctrine" of Ephesians -- 10.3.1. Functional Teleology and Ecclesial Unity -- 10.3.2. Functional Teleology and Cosmic Christology -- 10.3.3. Functional Teleology and Eschatology in Ephesians -- Chapter 11: Significance and Implications -- 11.1. Overview -- 11.2 Thomas Aquinas and the Interpretation of Ephesians -- 11.2.1. Aquinas, Teleology, and Ephesians' Auslegungsgeschichte -- 11.2.2. Aquinas and the Interrelation of Ephesians' Ecclesial Metaphors -- 11.2.3. Aquinas and the Teleological Conceptions of Hope, Completion, and Perfection -- 11.2.4. Aquinas, Teleology, and Inaugurated Eschatology -- 11.2.5. Reception History and Modern Biblical Studies -- 11.3. Implications: Ancient Philosophy, Early Christianity, and Ethics -- Bibliography -- Index of References -- Index of Modern Authors -- Subject Index
Description based on print version record
Keywords: Bible ; Ephesians ; Criticism, interpretation, etc; Electronic books; Hochschulschrift